Characterisation of cross-linked hydrogel structures for cartilage applications - Mishbak, Hussein (2018)
Alginate is a biocompatible natural hydrogel being explored to create cartilage replacements either on its own or as part of a composite material. Bioprinting technologies based on photopolymerization principles are being used make such structures. In this paper, the effect of functionalization time on the mechanical morphology, swelling and degradation characterization of cross-linked alginate hydrogel is investigated. Alginate, chemically-modified with methacrylate groups and different reaction times is considered, by dissolving functionalized alginate with 1.5% photoinitiator solution and crosslinked by ultraviolet (UV) light (8 mW/cm2). Results show that by increasing the functionalization time, it was possible to obtain alginate material with a high level of unsaturation resulting in a less porous structure with high mechanical properties and a reduction of swelling. The influence of increasing the prepolymer concentration, reaction time and the amount of photoinitiator (PI) on mechanical and biomimetic properties of resulting hydrogels led to increased mechanical stiffness when measured at 10% strain. The swelling ratio of Photocrosslinked alginate hydrogels was studied and initial findings link this behavior to functionalization reaction time.